Investigation of the 7Li(p, n) neutron fields at high energies. (October 2020) - Brückner, B.; Erbacher, P.; Göbel, K.; Heftrich, T.; Khasawneh, K.; Kurtulgil, D.; Langer, C.; Nolte, R.; Reich, M.; Reifarth, R.; Weigand, M.; Wiescher, M.; et al.
Abstract: The neutron activation method has been proven to be a well-suited tool for the investigation of neutron capture cross sections relevant for the main component of the s-process. Neutrons produced via the 7 Li(p, n) 7 Be reaction at a proton energy of Ep = 1912 keV can be used to recreate a quasi-stellar neutron energy distribution mimicking the astrophysical s-process scenario at kB T = 25keV. For the weak s-process, which takes place in massive stars at temperatures between kB T = 25 keV and kB T = 90 keV, the activation method has not yet been successful in recreating quasi-stellar neutron spectra. However, simulations show that the activation method can be improved in order to recreate a quasi-stellar neutron spectrum at different energies by linear combination of different neutron spectra. In order to verify these simulations the neutron fields of the reaction have to be measured at different proton energies.